Hubungan Antara Tingkat Pengetahuan dan Kepatuhan Penggunaan Obat pada Pasien Tuberkulosis di Salah Satu Puskesmas di Jakarta Pusat - Maifitrianti, Maifitrianti; Wiyati, Tuti; Apriliyanti, Netha Apriliyanti (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2024)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Non-compliance with TB treatment can lead to low cure rates, high mortality rates and increased risk of recurrence. Knowledge is very important for TB patients in order to sensitize patients to be compliant in carrying out treatment. This study aims to determine the relationship between knowledge level and adherence to taking medication in TB patients at the Kemayoran District Health Center for the period July - September 2023. This study used a cross sectional method with purposive sampling technique. Respondents of this study amounted to 108 patients, 105 patients met the inclusion criteria and 3 patients met the exclusion criteria. The level of knowledge was assessed using the knowledge questionnaire and the level of compliance was assessed using the Medication Adherence Rating Scale (MARS-5) questionnaire. The relationship between knowledge and adherence was analyzed using the Spearman Rho test. The results showed that most patients had good knowledge as many as 81 patients (77.1%) and patients were compliant in taking medication as many as 75 patients (71.4%). The results of bivariate analysis showed that the level of knowledge had a significant relationship with adherence to taking medication (p<0.05) with a strong correlation value (r 0.660) and positive direction.